Macroscopic monitoring of rotting and microbial growth in papaya 'Formosa': observation in the home environment as remote teaching practices (Research, Society and Development, 2022)
The papaya present rapid ripening and postharvest degradation. The monitoring of deterioration processes by contaminants and determination of microorganisms by quantification is a recurrent practice in higher education institutions. However, due to the Covid-19 Pandemic, it was necessary to apply other teaching methods. Thus, the objective of this resource was to validate a macroscopic accompaniment method of rotting and microbial growth in 'Formosa' papaya, stored in domestic environment, under two conditions of estimated temperatures: environment at 26±6°C and refrigerated 10±2 º C. The fruits of papaya 'Formosa' were obtained with a minimum of 75% of the yellow peel and transported to the domestic environment, where evaluations of the loss of mass and fungal growth in the fruits were performed by observing the development of mycelium. At the end, it was noticed that the mass loss was high at the last storage time (13 days), with 73.7% for fruits stored at room temperature and 39% for refrigerated fruits. There was growth of fungal structures and necrosis of up to 5.5 cm in the pulp and 4.3 cm peel in the last evaluation time (312h). It was concluded that the validation of the monitoring microbial growth method in fruits was feasible, there was a high level of deterioration in fruits at room temperature compared to refrigerated fruits and considerable differences were noticed for the loss of fruit mass in ambient conditions.